Decentralized Systems with Design Constraints - Mahmoud, Magdi S.; SpringerLink (Online service) (London : Springer London : Imprint: Springer, 2011)
Decentralized Systems with Design Constraints provides a rigorous framework for examining the analysis, stability and control of large-scale systems, and addressing the difficulties that arise because of dimensionality, information structure constraints, parametric uncertainty and time-delays. The achievements of this monograph are three-fold. It: ·         reviews past methods and results from a contemporary perspective; ·         examines present trends and approaches to provide future possibilities; and ·         investigates robust, reliable and/or resilient decentralized design methods based on a linear matrix inequalities framework. As well as providing an overall assessment of large-scale systems theories over the past several decades, the author presents key related concepts and efficient computational methods. Representative numerical examples, end-of-chapter problems, and typical system applications are included, and theoretical developments and practical applications of large-scale (interconnected) dynamical systems are discussed in depth.
Keywords: Control engineering; Electrical engineering; Computer communication systems; Vibration; Dynamical systems; Dynamics; Control and Systems Theory; Communications Engineering, Networks; Computer Communication Networks; Vibration, Dynamical Systems, Control